Links between José Ángel Valente’s Poetry and Spectral Music - Aguirre Martínez, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The ideas of limit and musicality constitute axial concepts in José Ángel Valente’s poetry. In this paper we propose to link Valente’s poetics with Spectral Music. We will review the foundations of José Ángel Valente’s maturity poetry with the purpose of comparing them with the theoretical approaches of Spectral Music.The fluctuating and permeable nature of the limit determines the foundations of Spectral Music as well as Valente’s poetics. We can establish that the notion of ‘reverberance’ constitutes the epistemological basis -even ontological- of those styles. The exploration of the own material nature is the way that both liminal aesthetics determine themselves as knowledge paths. The self-knowledge turns into aesthetic object.